NATAN MALLAYEV AND THE HISTORICAL-LITERARY SIGNIFICANCE OF FIFTEENTH-CENTURY TAZKIRAS - Temirova Anora Cho'yan kizi (Modern American Journals, 2025)
This article analyzes the views of Natan Mallayev on the first article of the collection of literary and critical articles "Issues of Uzbek Literature" published in the 1st issue of 1959, namely, "The Historical and Literary Significance of the 15th Century Tazkiras" by Davlatshah Samarkandi. The article analyzes the works of Muhammad Avfiy's "Lubob ul-albob", Jomi's "Bahoristan", Davlatshah Samarkandi's "Tazkirat ush-shuaro", and Alisher Navoi's "Majolis un-nafois". In his article “The Historical and Literary Significance of the 15th Century Tazkiras,” N. Mallayev provided the necessary information about the emergence of tazkira writing in the 9th century, the fact that tazkira works were first created in Arabic, and later in Persian-Tajik, and that Alisher Navoi laid the foundation for Uzbek tazkira writing with his work “Majolis un-nafois.” In the process of researching the work of Davlatshah Samarkandiy “Tazkirat ush-shuaro” (Tazkir of Poets), N. Mallayev analyzed this tazkira based on the earliest sources, namely the 1320 x copy copied by Muhammad Yusufkhan Qurbanniyoz.
Keywords: tazkira,